ACTIVE METHODS OF CHECKING HOMEWORK IN PRIMARY SCHOOL - Akhmedova Mushtariybonu Makhmudjonovna (Bright Mind Publishing, 2025)
Article explores the use of active methods for checking homework in primary school. The work analyzes the theoretical basis of homework as a pedagogical tool and examines innovative ways of its assessment in classroom practice. The study identifies the advantages of active methods – such as peer checking, gamification, and digital platforms – in increasing students’ motivation, responsibility, and self-reflection. Experimental results demonstrate that active methods make the learning process more engaging and effective.
Keywords: homework, primary school, active methods, peer assessment, motivation, feedback, interactive learning.